To engage students on safety, keep it light but informative. Issue 5 (15th August 2019) - Enos, Gary
Abstract : PALM BEACH GARDENS, FLA. — Promoting events with engaging marketing and a close linkage with Student Life can raise the profile of campus safety initiatives that students might otherwise ignore, a pair of presenters from Broward College told an audience at the Association of Florida Colleges' Campus Safety Symposium in July.